INNOVATION PROCESSES IN NEW PRODUCT DEVELOPMENT: MODELS FOR CREATIVE INDUSTRY IN INDONESIA - Efrata, Tommy Christian; Radianto, Wirawan E. D; Marlina, Maria A. E.; Dewi, Shinta K. (Jurnal Aplikasi Manajemen, 2020)
The growth of service companies in the scope of the creative industries has grown a lot in this decade. However, not much research has explored the innovation pro- cess that is key to business sustainability. This study builds the model of the innovation process performed by selected service companies within the creative industry. It investigates some processes of new product development (NPD) of service products of the firms. An interview was conducted on the companies'owners or directors with sufficient knowledge of the innovation process implemented in each company. Data were processed using a qualitative method approach with the help of the NVIVO program. The outcome revealed similarities in the innovation process of NPD among companies, specifically in the stages of identifying problems and opportunities, generating and processing ideas, market predictions, business analysis, visualization, and execution, representing the model in service companies. This research outcome would benefit business practitioners and scholars to better comprehend the NPD process in service companies within the creative industries.